Analyzing Indian general public's perspective on anxiety, stress and trauma during Covid-19 - A machine learning study of 840, 000 tweets. Issue 3 (May 2021) - Praveen, S.V.; Ittamalla, Rajesh; Deepak, Gerard
Abstract: Background and aims: Ever since COVID-19 was declared a pandemic by WHO in late March 2020, more and more people began to share their opinions online about the anxiety, stress, and trauma they suffered because of the pandemic. However, very few studies were conducted to analyze the general public's perception of what causes stress, anxiety, and trauma during COVID-19. This study focuses particularly on understanding Indian citizens. Methods: By using Machine learning techniques, particularly Natural language processing, this study focuses on understanding the attitude of Indian citizens while discussing the anxiety, stress, and trauma created because of COVID-19 and the major reasons that cause it. We used Tweets as data for this study. We have used 840, 000 tweets for this study. Results: Our sentiment analysis study revealed the interesting fact that, even while discussing about the stress, anxiety, and trauma caused by COVID-19, most of the tweets were in neutral sentiments. Death and Lockdown caused by the COVID-19 were the two most important aspects that cause stress, anxiety, and Trauma among Indian citizens. Conclusion: It is important for policymakers and health professionals to understand common citizen's perspectives of what causes them stress, anxiety, and trauma to formulate policies and treat the patients. Our study shows that Indian citizens use social media to share their opinions about COVID-19 and as a coping mechanism in unprecedented time. Highlights: Most social media posts of Indians discussing stress, anxiety, and trauma caused by COVID-19 were neutral. Deaths caused by COVID-19 and lockdown were two key issues that cause stress, anxiety, and Trauma among Indian citizens. Indian citizens use social media to share their opinion and to encourage each other during COVID-19.